Conciencia sobre el cuidado del medio ambiente en niños de la Institución Educativa Inicial N° 728 Caballo Cocha 2021 - Oliveira Lopez, Katrin Mariel (2023)
The following summary is presented considering the main question and objective of the research: How is the awareness about caring for the environment in children aged four and five in the Initial Educational Institution No. 728 Caballo Cocha 2021? And the main objective of the research was to describe the level of awareness about caring for the environment in children aged four and five in the Initial Educational Institution No. 728 of Caballo Cocha in 2021. The type of research was descriptive and as a design it was field, univariate, and cross-sectional. The population and sample of the investigation were 60 children of three and four years. The observation technique and observation guide were applied to obtain the data. Expert judgment was applied to the data collection instrument. The results show that the level of awareness in the care of the environment in children of four and five years in the Initial Educational Institution No. 728, is of an average level in 88.3% while it is of a high level in 11.7%.